Cutoff interference polymer-crystalline multilayer systems with the passband edge smooth tuning - Belyaeva, A.I.; Kolomiets, S.N. (Functional Materials, 2005)
The smooth tuning possibility of the passband edge in an interference polymer-crystalline cutoff filter has been studied. This is attained by using the periodic polymer (£) — germanium (H) structures of uneven optical thickness, i.e., the systems of the [[HH±C)(L±C)k(L±C)k(H±C) type where H and L are quarter-wave layers of high and low refractive index, respectively; C in the thickness unequality parameter; k, an integer. The effect of the C value variation from 0 to 0.3 H on the optical properties of polyethylene-germanium interference structures have been studied theoretically and in experiment. A method has been developed to smooth the secondary extremes in the uneven thickness polyethylene-germanium systems by adding auxiliary polyethylene interference layers.